Consortium neuroscience of attention deficit/hyperactivity disorder and autism spectrum disorder: The ENIGMA adventure. Issue 1 (18th May 2020) - Hoogman, Martine; van Rooij, Daan; Klein, Marieke; Boedhoe, Premika; Ilioska, Iva; Li, Ting; Patel, Yash; Postema, Merel C.; Zhang‐James, Yanli; Anagnostou, Evdokia; Arango, Celso; Auzias, Guillaume; et al.
Abstract: Neuroimaging has been extensively used to study brain structure and function in individuals with attention deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) over the past decades. Two of the main shortcomings of the neuroimaging literature of these disorders are the small sample sizes employed and the heterogeneity of methods used. In 2013 and 2014, the ENIGMA‐ADHD and ENIGMA‐ASD working groups were respectively, founded with a common goal to address these limitations. Here, we provide a narrative review of the thus far completed and still ongoing projects of these working groups. Due to an implicitly hierarchical psychiatric diagnostic classification system, the fields of ADHD and ASD have developed largely in isolation, despite the considerable overlap in the occurrence of the disorders. The collaboration between the ENIGMA‐ADHD and ‐ASD working groups seeks to bring the neuroimaging efforts of the two disorders closer together. The outcomes of case–control studies of subcortical and cortical structures showed that subcortical volumes are similarly affected in ASD and ADHD, albeit with small effect sizes. Cortical analyses identified unique differences in each disorder, but also considerable overlap between the two, specifically in cortical thickness. Ongoing work is examining alternative research questions, such as brain laterality, prediction of case–control status, and anatomical heterogeneity. In brief, great strides have been made toward fulfilling the aims of the ENIGMA collaborations, while new ideas and follow‐up analyses continue that include more imaging modalities (diffusion MRI and resting‐state functional MRI), collaborations with other large databases, and samples with dual diagnoses.